(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In today’s scenario, the shipping and logistic sector is one of the fastest growing sectors and a lot of funds are invested in this sectors. Also today’s the logistic company is becoming more complex. So, there is a strong need to evaluate their performance of the logistic company. There are various Analysis to evaluating the performance of the logistic company , but in this study we discussed about the ratio analysis to evaluate the performance of the familier logistic company. This analysis measures the performance of the logistic company from parameter comprising of Inventory turnover ratio, Asset turnover ratio , Current ratio, Debt equity ratio ,Operating profit per share, , We have studied the performance of five logistic company selected on the basis of management efficiency (i.e. Blue Dart Express,Agarwl Packers and Movers, Allcargo Logistics, Sical logistic Ltd. ). Period under study is from 2015 to 2019.From the weighted results of each ratio, we have given marks on the bases of the performance of the logistic company.